The optimal drying temperature and moisture content for microwavable job's tears grains - Orathai Bunthawong (2018)
This research focused on the optimal drying temperature and moisture content for two forms - polished and unpolished - of microwavable, puffed, black husk variety, Job's tears grains. Grains were prepared by overnight soaking and autoclave cooking at 15 psi for 20 minutes. All prepared grains were then dried in a tray dryer at five different temperatures (60, 70, 80, 90, and 100°C). After drying and overnight storage at room temperature, their moisture content was determined. The pretreated grains at different moisture contents were puffed by microwave oven at the maximum power of the machine (800 watts) for 1 to 3 minutes, or until they were completely expanded. If the expansion ratios of both forms of puffed products were greater than or equal to 1.5, the puffed products were accepted by taste panelists; accordingly, we selected the expansion ratio of 1.5 as the benchmark for these puffed products. At this benchmark expansion ratio, the optimal drying condition of pretreated Job's tears grains was 90°C for 2 hours, resulting in 9.4% to 10.3% moisture content for polished and unpolished grains, respectively.